(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Survey the rate of Rubella vaccination and associated factors among pregnant women at Le Van Thinh Hospital in 2024. Methods: A cross-sectional study was conducted on 253 pregnant women at Le Van Thinh Hospital from March 2024 to April 2024. A convenience sampling method was used. The information was collected through face-to-face interviews using a structured questionnaire. Data analysis included descriptive statistics by frequency and percentage, and using Chi-square and Fisher’s exact test to determine factors associated with Rubella vaccination among pregnant women. Results: In a study involving 253 pregnant women, the rate of pregnant women vaccinated against Rubella was 35.2%, and the rate of pregnant women with general knowledge about the disease and general knowledge about Rubella vaccine were 52.2% and 60.5% respectively. There was a relationship between Rubella vaccination and factors including educational level, family economic situation, occupation, number of children, knowledge of Rubella disease, and vaccine. Conclusion: The rate of Rubella vaccination among pregnant women remains low. There are many misconceptions of knowledge about Rubella disease and vaccine. It is necessary to enhance the communication of health education and encourage Rubella vaccination before pregnancy for women of childbearing age and women planning to become pregnant to improve vaccine coverage to prevent disease in pregnant women and CRS in children.